Biofilm formation following chitosan-based varnish or chlorhexidine-fluoride varnish application in patients undergoing fixed orthodontic treatment: a double blinded randomised controlled trial - Preethi Poornima; Jogikalmat Krithikadatta; Ratna Rachel Ponraj; Natanasabapathy Velmurugan; Anil Kishen (BMC, 2021)
Abstract Background Orthodontic treatment poses an increased risk of plaque accumulation and demineralisation of enamel leading to white spot lesion around the brackets. This parallel arm trial aims to assess the degree of bacterial plaque formation adjacent to orthodontic brackets, following the application of a chitosan-based varnish or chlorhexidene-fluoride varnish. Methods A total of 200 teeth from 20 patients undergoing fixed orthodontic therapy were assessed and biofilm formation around the brackets were recorded using the Bonded Bracket Index (Plaque index) at baseline and weekly for 6 weeks. The bacterial count and plaque pH at corresponding weekly intervals were also recorded. Following bracket bonding, the patients were cluster randomised to receive chitosan-based varnish-CHS (UNO Gel Bioschell, Germiphene corp., Brantford, Canada) or chlorhexidine-fluoride varnish-CFV (Cervitec F, Ivoclar Vivadent, Schaan, Liechtenstein) every week on the representative teeth respectively. BBI proportions were compared between groups at all time intervals using Chi square test. Mean plaque bacterial count and plaque pH were compared using Mann Whitney U test and Tukey's HSD test respectively. Results Baseline characteristics were similar between the groups: Mean age was CHS = 23 and CFV = 21; male to female ratio was CHS = 5/5, CFV = 7/3. At the end of 6 weeks, chitosan-based varnish performed equal to chlorhexidine-fluoride varnish (P > 0.05) with 98% and 95% of teeth with acceptable scores respectively. The plaque bacterial count significantly reduced at 6 weeks for both varnish compared to the baseline; The value for CHS was 0.43 ± 0.4 × 104 and CFV was 0.77 ± 0.64 × 104 CFU (P < 0.05), with no difference between both the varnishes. Both varnishes had no effect on the plaque pH that remained neutral. Conclusion This trial showed that both chitosan-based varnish and chlorhexidine-fluoride varnish reduced bacterial count, while the plaque pH remained neutral over a period of six weeks in patients undergoing fixed orthodontic therapy. The anti-plaque effects of the natural biopolymeric chitosan-based varnish was similar to that of chlorhexidine-fluoride varnish, a known chemotherapeutic agent. Registration: This trial protocol was registered with https://www.ctri.nic.in (CTRI/2019/05/018896). (Date of registration 02/05/2019). Protocol: The protocol was not published before trial commencement.